2008
DOI: 10.1007/bf03349257
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss in Turner syndrome: Results of a multicentric study

Abstract: One hundred and seventy-three pts, mean chronological age (CA) 12+/-6.2 yr. Patients were submitted to different therapies: GH, estrogen therapy (EE), no therapy (no tx). Seventy-nine pts (CA 11 yr) had no otological diseases. Conductive hearing loss (CHL) occurred in 38.7% (CA 11 yr) and otoscopy was: persistent secretory otitis media in 55.2%, chronic otitis media in 10.4%, pars flaccida retraction pocket in 19.4%, mostly bilateral. Cholesteatoma was present in 15%. Sensorineurinal hearing loss (SNHL) occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 25 publications
2
36
1
1
Order By: Relevance
“…In younger patients, CHL occurred in 38% and persistent secretory otitis media in 55%. SNHL frequency was similar (94).…”
Section: Ent Problemsmentioning
confidence: 77%
See 1 more Smart Citation
“…In younger patients, CHL occurred in 38% and persistent secretory otitis media in 55%. SNHL frequency was similar (94).…”
Section: Ent Problemsmentioning
confidence: 77%
“…(93,95). In younger patients, CHL was more common (94). Recent guidelines have recommend screening at least every 2-3 years in all asymptomatic patients, and more frequently in those with established hearing loss or new symptoms of hearing problems (2).…”
Section: Autoimmune Diseases During Transitionmentioning
confidence: 99%
“…4,5,7 Some reports suggest that CHL is associated with impaired Eustachian tube function resulted from congenital craniofacial abnormalities. 14,18 As for the correlation between variable karyotype abnormality and CHL in TS, various authors 8,14,18 have reported that monosomy 45,X and 45X/46Xi(Xq) are strongly associated with CHL. However, our study did not reveal a significant correlation between CHL and monosomy 45,X or variable craniofacial anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…17 The common reasons for conductive hearing loss (CHL) in TS patients are recurrent OM with effusion, chronic OM, cholesteatoma formation (likely as the result of failure of the Eustachian tube associated with lymphedema 4 ), and the actual anatomic shortening of the skull base or congenital craniofacial abnormalities. 18 Several case studies suggest that monosomy 45,X 8,14,18 or isochromosome 46,i(Xq) 8 is significantly associated with CHL in TS patients.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, estrogen deficiency may affect the hearing function of women [16,17] . In the laboratory, bilateral ovariectomy in female rats may be an appropriate approach to simulate the effects of estrogen deficiency on hearing function [18,19] .…”
Section: Introductionmentioning
confidence: 99%